Eliciting selves: narrating collective redemption through historical representation - Lynn, Vanessa (Critical criminology, 2022)
This article reports the results of a research study which sought to understand how formerly incarcerated Black and Brown men make sense of their experience of prison rehabilitation and the desistance process—one that entails rebuilding individual identity as a reformed individual. Drawing on life histories and photo-elicitation interviews with twenty-three formerly incarcerated Black and Brown men, this study sought to assess the extent to which knowledge of Black history matters in building identity. This article highlights two narrative forms that emerged from the men’s responses to photographs of famous Black leaders, which helps further our understanding of desistance as a relational process of creating collective belonging in prosocial racialized communities. The first is the retrospective narrative of prison organizing. This refers to narrative identities that emerged as the participants talked about taking on leadership and organizational roles while incarcerated, thus creating communities of meaning around understanding the self through Black history. The second is the prospective narrative of togetherness, where the participants’ narrative identities expressed a longing for a sense of togetherness (or wanting to belong)—achieved through becoming individual agents of social change. This article provides new possibilities for understanding desistance as a collective process, as well as recommendations for using photo-elicitation as a narrative intervention.